Experimenting in Geography Education. Competencies of Secondary School Students - Peter, Carina; Sprenger, Sandra (Journal of Geography Education, 2014)
In geography lessons, students should be able to reflect and describe the methodic steps of experimenting. Four competencies are described in the methodology of experimenting: a) identification of the problem – formulating the correct question, b) generating hypotheses, c) planning and performing experiments and d) evaluating data. In this study, we investigated the assessment and the grade of competencies in secondary education of these experimenting skills. We measured these four skills by a paper-and-pencil test with 29 items. The results show significant difficulties in all phases of the inquiry process, appropriate interventions are highly needed.
Keywords: experiment, competencies, formulating the question, generating hypotheses, planning and experiments, evaluating data, inquiry learning, geography education